Comparison of Effectiveness of Topiramate and Diazepam in Preventing Risk of Recurrent Febrile Seizure in Children underAge of 2 Years - Fayyazi, Afshin; Khajeh, Ali; Baghbani, Ashraf (Iranian Journal of Child Neurology, 2018)
Background and Objective: Febrile seizures are the most common type of convulsions. Medicinal prophylaxis is sometimes used for children at high risk of recurrent febrile seizure. In certain circumstances, conventional drugs such as diazepam and phenobarbital cannot be used and the need for alternative medicines is felt. This study set out to compare the effectiveness of topiramate and diazepam in preventing the risk of recurrent febrile seizure in children under the age of 2 years. Methodology: This was a randomized controlled trial. The research sampleincluded 54 patients, at risk of recurrent febrile seizure,who were inhibited from taking phenobarbital. After selection, they were randomly divided into two groups. The first group received diazepam treatment during fever episodes and the second group received daily dose of topiramate. A one-year follow-up of recurrent febrile seizure and its complications was also conducted. Findings: Thirty four patients (17 patients in each group) completed the one-year course of the trial. Recurrent febrile seizure was not observed in the course of preventive treatment. The prevalence of minor complications was 29.4% in the diazepam group and 48.5% in the topiramate group.No major complication was observed in among the subjects Conclusion: Topiramate can be recommended for preventing recurrent febrile seizure when the use of front line medicines is not possible.